2015
DOI: 10.1039/c5qi00126a
|View full text |Cite
|
Sign up to set email alerts
|

Nanosheet-assembled MoSe2 and S-doped MoSe2−x nanostructures for superior lithium storage properties and hydrogen evolution reactions

Abstract: The development of layered molybdenum chalcogenides with largely exposed active sites is receiving intense interest because of their potential applications in energy storage and catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Thus, it would be possible to achieve a thermoneutral state (Δ G H ≈ 0) by designing ternary alloyed MoS 2 x Se 2(1− x ) nanosheets with an optimized S/Se ratio. Improved HER activity has been experimentally demonstrated in S‐doped MoSe 2 nanosheets . Li et al reported a solvothermal route to synthesize a series of MoS 2 x Se 2(1− x ) nanosheets with tunable chalcogen composition.…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
“…Thus, it would be possible to achieve a thermoneutral state (Δ G H ≈ 0) by designing ternary alloyed MoS 2 x Se 2(1− x ) nanosheets with an optimized S/Se ratio. Improved HER activity has been experimentally demonstrated in S‐doped MoSe 2 nanosheets . Li et al reported a solvothermal route to synthesize a series of MoS 2 x Se 2(1− x ) nanosheets with tunable chalcogen composition.…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
“…As a result, large numbers of accessible active sites can be achieved for surface charge storage, fast kinetics, and rapid relax of structural strain induced by the Li insertion . Various TMDs with hollow structures have been synthesized and then used as anode materials for LIBs, including MoS 2 microboxes, C@MoS 2 nanoboxes, MoS 2 tubular structures, MoS 2 /C microspheres, MoS 2 hollow nanospheres, MoS 2 yolk‐shell structures, and MoSe 2− x nanotubes . Recently, Lou and co‐workers compared the electrochemical performance of the hollow MoS 2 microbox and solid MoS 2 microparticle, and found that the hierarchical MoS 2 microbox exhibited stable cycling performance and a high discharge capacity of 900 mAh g −1 after 50 cycles at a current density of 100 mA g −1 .…”
Section: Rechargeable Batteriesmentioning
confidence: 99%
“…Thus, it is challenging to controllably synthesize edge‐terminated TMD structures. The construction of hierarchical 3D TMD architectures is an alternative to address this issue, since more edge sites can be exposed . For example, 3D MoS 2 nanoflowers with a high specific surface area of 431.2 m 2 g −1 exhibited an improved HER activity with an onset potential of 100 mV and a Tafel slope of 80.5 mV dec −1…”
Section: Electrocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…A pure 200 nm-thick Ag film (labeled as Ag) exhibited 588 mV at 10 mA·cm −2 , as shown in Figure 5a. In earlier studies, HER properties were demonstrated for the various layer materials including, bulk and their exfoliated layers of TMD materials such as high-quality monolayer MoS 2(1−x) Se 2x (η 10 mA·cm −2 = 273–300 mV) [19], S-doped MoSe 2−x nanotubes and MoSe 2 nanocaterpillars (η 2 mA·cm −2 = 95–318 mV) [20], tungsten selenide thin films deposited on tungsten foils (η 10 mA·cm −2 = 350 mV) [21], electrodeposition of amorphous cobalt–cobalt oxide/cobalt selenide (CoO x –CoSe) composite film on a 3-dimensional porous Ni foam (NF) (η 10 mA·cm −2 = 300–380 mV) [22], and electrodeposited cobalt selenide nanostructures (η 10 mA·cm −2 = 472–481 mV) [23].…”
Section: Resultsmentioning
confidence: 99%